Physiotherapy Management of Total Knee Replacement et Causa Bilateral Genu Osteoarthritis - Reski, Sri; Wahyuni, Wahyuni; Widiatmi, Sri (Universitas Muhammadiyah Surakarta, 2023)
Background: Total Knee Replacement (TKR) et causa Osteoarthritis genu bilateral is a medical procedure for replacing the knee joint with an artificial material in the form of a plate. Weight gain or obesity may be the most common cause of meniscus/joint-cushion thinning. This will cause pain and limited range of motion after knee joint replacement surgery. By providing physiotherapy interventions in the form of IR, Tens and Exercise therapy based on the Rehabilitation Protocol For Knee Replacement Surgery, it is hoped that pain and functional limitations in the knee can return to normal soon. Purpose: the aim is to determine the effect of providing physiotherapy interventions in the form of IR, Tens and Exercise therapy in increasing functional ability in conditions after Total Knee Replacement (TKR) and causing bilateral genu osteoarthritis. Methods: this program is carried out directly to respondents with post-Total Knee Replacement (TKR) conditions and causes of bilateral genu osteoarthritis by administering 3 times of therapy to obtain results of increased functional ability as measured by scores on the KOOS index, namely T0: 36.406 to T3: 39.554. Conclusion: the provision of physiotherapeutic interventions in the form of IR, Tens and Exercise therapy after the case of Total Knee Replacement (TKR) et causa osteoarthritis genu bilateral is proven to reduce complaints in the form of edema, pain, limited range of motion of the joints, and decreased muscle strength which has an impact on increasing the functional abilities of the respondents.